Faktor-Faktor yang Mempengaruhi Keputusan Petani dalam Pengambilan Kredit di LPD Desa Pakraman Timbul Kecamatan Tegallalang Kabupaten Gianyar - SUSANTIANI, NI KADEK; DARMAWAN, DWI PUTRA; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.1, Juli 2021, 2021)
Factors Influencing Farmers Decisions in Credit Collection in the LPD of Pakraman Timbul Village Tegallalang District Gianyar Regency The village credit institution (LPD) is a form of the Pakraman village community movement to be able to improve the economic standard of living of the Pakraman village community itself. The purpose of this study was to determine the factors that influence farmers decisions in taking credit and the most dominant factor influencing farmers decisions in taking credit in the LPD  of  Pakraman Timbul Village. The data in this study consisted of qualitative and quantitative data obtained from primary data sources and secondary data. The sampling technique was done by accidental sampling and obtained 50 respondents. The analysis technique used is SEM-PLS. The dependent variable (Y) is the farmers decision and the independent variable (X) is the interest rate, service, credit distribution procedure, repayment period and guarantee. The results showed that the variable interest rates, service and repayment period had a significant effect while the procedure for lending and collateral had no significant effect. The dominant variable that influences farmers decision to take credit in LPD Pakraman Timbul is the interest rate variable.  Suggestions for this research are expected to be able to pay attention to LPD interest rates offered. Good interest rates are supported by friendly service and appropriate retention periods. Credit lending procedures are expected to be straightforward and guarantees can be properly valued.